Perspektif Al-Quran tentang Pluralisme: The Quranic Perspective on Pluralism - Ruslan, Ruslan (Dirasat Islamiah: Jurnal Kajian Keislaman, 2023)
Pluralism emphasizes diversity and acceptance of differences, which can cause several potential problems. One of them is the potential for social conflict due to differences in understanding and interpretation of religious, cultural, or ideological values. In addition, pluralism can also trigger competition between groups who want to be the center of attention or claim their truth. This study discusses pluralism in the Qur'an, focusing on the meaning of pluralism, types of pluralism, and its implications for everyday human life. This literature review found that the Quran expresses pluralism in various forms, namely the pluralism of God's creatures, ethnicity, language, religion, party, resources, and profession. With various forms stated by the Quran, pluralism has implications for society, namely that pluralism is sunnatullah, freedom of religion, positive interaction, and competing to do good.